The Implementation of Artificial Intelligence in South African Higher Education Institutions: Opportunities and Challenges - Patel, Shahiem; Ragolane, Mahlatse (Technium Education and Humanities, 2024)
This paper examines the strategic implementation of Artificial Intelligence (AI) in South African Higher Education (HE) institutions and its potential opportunities and challenges. It posits that AI can significantly enhance educational outcomes and administrative efficiency in South African HE institutions, but successful integration necessitates addressing infrastructure limitations, ethical concerns, and strategic frameworks. The study employs a qualitative research methodology using secondary sources. Findings reveal substantial benefits, such as improved administrative efficiency, personalized learning, and data-driven decision-making, often impeded by challenges like inadequate infrastructure, socio-economic disparities, and ethical issues related to data privacy and algorithmic bias. The importance of strategic planning and frameworks, such as the AI8-Point Model, is emphasized for effective AI integration in HE. Recommendations include investing in technological infrastructure, developing policies for ethical and privacy concerns, and adopting strategic frameworks. Collaboration among policymakers, educators, and technology providers is essential to navigate AI integration complexities and enhance educational outcomes and operational efficiency in South African HE.